Penerapan Pelayanan Publik Berbasis Digital Melalui Website Digikel di Kelurahan Biawao & Limba U1 Kota Gorontalo - Israwati Salsabila Karsimin; Irawaty Igirisa; Alfiyah Agussalim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to examine and analyze the implementation of digital-based public services through the Digikel website in Biawao Village and Limba U1 Village,Gorontalo City. The main focus of this study includes three aspects:(1) support, (2)capacity, and (3) value. This study employs a qualitative approach with a descriptiveresearch design. Data were collected through observation, interviews, and documentation. The study's findings indicate that the implementation of the Digikel website hasbeen effective across the three aspects. (1) Support: The implementation of Digikelis supported by leadership commitment, active employee involvement, and policysupport from the city government through clear regulations. However, there are stillchallenges in the community's socialization process, which has not been optimal.(2) Capacity: Human resources in Biawao Village and Limba U1 Village are considered to have adequate competence through technical guidance. Nevertheless,there are still infrastructure-related obstacles, including unstable internetconnectivity and limited computer equipment. The absence of a dedicated budgetat the village level has also been a constraint in system development. (3) Value: The implementation of Digikel has had a positive impact, particularly in improving efficiency in terms of time, cost, and labor, as well as in accelerating, simplifying, and enhancing the transparency of public services. However use of this system has not yet been fully optimized due to low levers of diritalitgacy among somemembers of the community.